On a theorem of B. Keller on Yoneda algebras of simple modules - Jasso, Gustavo (Comptes Rendus. Mathématique)
A theorem of Keller states that the Yoneda algebra of the simple modules over a finite-dimensional algebra is generated in cohomological degrees $0$ and $1$ as a minimal $A_∞ $-algebra. We provide a proof of an extension of Keller’s theorem to abelian length categories by reducing the problem to a particular class of Nakayama algebras, where the claim can be shown by direct computation.